2022
DOI: 10.1038/s41398-022-01985-z
|View full text |Cite
|
Sign up to set email alerts
|

Deleterious effects of nervous system in the offspring following maternal SARS-CoV-2 infection during the COVID-19 pandemic

Abstract: During the Coronavirus disease 2019 (COVID-19) pandemic, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is universally susceptible to all types of populations. In addition to the elderly and children becoming the groups of great concern, pregnant women carrying new lives need to be even more alert to SARS-CoV-2 infection. Studies have shown that pregnant women infected with SARS-CoV-2 can lead to brain damage and post-birth psychiatric disorders in offspring. It has been widely recognized that SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…In addition, another meta-analysis study has reported that preventing or safely treating maternal infections could reduce the incidence of ASD by 12% to 17% [ 24 ]. Moreover, the infection of coronavirus disease 2019 (COVID-19) during pregnancy is associated with MIA and can result in the risk of ASD onset by alteration of maternal and fetal immune responses [ 9 , 11 , 25 , 26 ]. Therefore, a thorough understanding of the role of inflammation and oxidative stress in the pathogenesis of ASD has also gained significance.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, another meta-analysis study has reported that preventing or safely treating maternal infections could reduce the incidence of ASD by 12% to 17% [ 24 ]. Moreover, the infection of coronavirus disease 2019 (COVID-19) during pregnancy is associated with MIA and can result in the risk of ASD onset by alteration of maternal and fetal immune responses [ 9 , 11 , 25 , 26 ]. Therefore, a thorough understanding of the role of inflammation and oxidative stress in the pathogenesis of ASD has also gained significance.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological data suggest that maternal immune activation (MIA), such as maternal infection, might be associated with the risk of neuropsychiatric disorders, such as schizophrenia and ASD in offspring [ 110 , 111 ]. During the coronavirus disease 2019 (COVID-19) pandemic, an increasing number of pregnant women have become infected with COVID-19 worldwide, and MIA induced by COVID-19 infection has been suggested as a risk factor for schizophrenia and ASD [ 112 114 ]. A cohort study shows that severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) exposure in utero may be associated with neurodevelopmental sequelae in some offspring [ 115 ].…”
Section: Introductionmentioning
confidence: 99%
“…These viruses cause brain damage primarily through maternal immune activation(MIA), the activation of the placental and fetal immune systems, and then the activation of the fetal brain immune system (neuroinflammation) [ 50 , 51 ]. SARS-CoV-2 can potentially affect the growth and development of the fetal nervous system through maternal immune activation [ 52 ]. The flu did the same; an increased rate of neurological disorders, including schizophrenia, has been reported in adults who were fetuses during the 1957 influenza pandemic [ 51 ].…”
Section: Maternal Covid-19 Infection and Its Fetal Neurological Outcomesmentioning
confidence: 99%
“…Maternal immune activation is associated with elevated levels of inflammatory cytokines. Cytokines can pass through the placenta and the blood-brain barrier and impair neural development in the fetus [ 52 ]. Neurotoxic properties of Cytokines may be mediated by an increase in reactive oxygens and a decrease in monoamine transport [ 1 ].…”
Section: Maternal Covid-19 Infection and Its Fetal Neurological Outcomesmentioning
confidence: 99%